2019
DOI: 10.1111/trf.15254
|View full text |Cite
|
Sign up to set email alerts
|

Anemia induces gut inflammation and injury in an animal model of preterm infants

Abstract: BACKGROUND While very low birth weight (VLBW) infants often require multiple red blood cell transfusions, efforts to minimize transfusion‐associated risks have resulted in more restrictive neonatal transfusion practices. However, whether restrictive transfusion strategies limit transfusions without increasing morbidity and mortality in this population remains unclear. Recent epidemiologic studies suggest that severe anemia may be an important risk factor for the development of necrotizing enterocolitis (NEC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 75 publications
(209 reference statements)
2
36
0
Order By: Relevance
“…In our cohort, the similarity in intestinal microbiome between the anemia and non-anemia groups during the first postnatal month suggested that the differences in perinatal factors and in the early antibiotic exposure were less likely to influence the subsequent differences in their microbiomes. The changes toward a dysbiotic microbiome together with a decline in Hct levels in anemic infants, warrant further investigations, especially in light of the findings in preclinical models (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, the similarity in intestinal microbiome between the anemia and non-anemia groups during the first postnatal month suggested that the differences in perinatal factors and in the early antibiotic exposure were less likely to influence the subsequent differences in their microbiomes. The changes toward a dysbiotic microbiome together with a decline in Hct levels in anemic infants, warrant further investigations, especially in light of the findings in preclinical models (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…In very low birth weight (VLBW) infants, anemia has been implicated in the development of necrotizing enterocolitis (NEC), a severe inflammatory and necrotic bowel disease of prematurity with high rates of morbidity and mortality (1,2). More recent studies show that mucosal inflammation and injury, the hallmarks of NEC, are present in infants with anemia (3,4) and neonatal mouse models demonstrate that anemia itself is pro-inflammatory (5,6). In addition, one mouse model indicates that the severity of NEC correlates with the severity of anemia (6).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple observational studies have reported an association between severe anemia and the development of NEC [34][35][36]. Anemia can impair splanchnic perfusion and increase intestinal inflammation and barrier disruption leading to tissue hypoxia and anaerobic metabolism and thus predisposing to ischemic injury and possibly to NEC [37][38][39][40]. Thus, preventing anemia could be a strategy to prevent the development of NEC, and RBC transfusion is a commonly used method to achieve this [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the critical value for abdominal tissue desaturation is noted when the HCT is less than 24%, predisposing premature infants for necrotizing enterocolitis and intestinal injury. [23][24][25] AOP also reported to be associated with increased incidence of intermittent hypoxic episodes in premature infants, especially after the first month of life, and RBC transfusions has been associated with reduction in apnea frequency in the short term. 26,27 In our study, premature infants with severe AOP during initial PO were more premature at birth, compared with controls.…”
Section: Discussionmentioning
confidence: 97%